Australian Technical Teachers' Experience of Technology Integration in Teaching. (August 2016) - Khan, Md. Shahadat Hossain; Bibi, Shaista; Hasan, Mahbub
This study investigated teachers' conceptions of technology integration into their teaching from two renowned technical and vocational education (TVE) institutes in New South Wales, Australia. Thirteen teachers were interviewed using qualitative techniques informed by the phenomenographic approach. The analysis of the data revealed that TVE teachers perceived the use of technology in teaching in four qualitatively different ways: (a) upgrading teacher knowledge, (b) ease of communication, (c) effective teaching, and (d) flexible teaching. Some findings align with existing phenomenographic studies of teachers' conceptions held in the context of university education. This study contributes to teachers' conceptions literature by identifying "flexible teaching" as one of the most significant conceptions of teaching within the context of TVE teaching in particular and higher education in general. The findings of the study could have an impact on teaching practice and faculty development programs in both TVE and other higher educational institutes.